An Investigation of Renewable Energy Solutions for Off-Grid Sustainable Housing in Rural Nigeria - Unegbu, Hyginus C. O.; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Journal of Sustainable Construction, 2024)
This study examines the adoption of renewable energy solutions for off-grid sustainable housing in rural Nigeria, focusing on the types of technologies implemented, their impact on living standards, and the factors influencing adoption. A mixed-methods approach, combining quantitative survey data from 340 households with qualitative interviews and case studies, reveals that solar photovoltaic (PV) systems are the most widely adopted renewable energy technology, significantly enhancing health outcomes, economic activities, and educational opportunities. Multivariate regression analysis identifies income, education level, and awareness as key predictors of renewable energy adoption, with coefficients of 0.345, 0.267, and 0.453, respectively, suggesting that higher income, education levels, and awareness substantially increase the likelihood of adopting renewable energy solutions. Structural Equation Modeling (SEM) illustrates that awareness mediates the impact of income and education on adoption, which, in turn, contributes to improved living standards. The study underscores the need for comprehensive policies, community engagement, capacity building, financial support, and effective monitoring and evaluation frameworks to encourage renewable energy adoption in rural Nigeria. These findings highlight the multifaceted benefits of renewable energy, including improved health, economic growth, and educational outcomes, while suggesting that addressing identified barriers can enhance the effectiveness and scalability of renewable energy initiatives.